DIGITAL EDUCATIONAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS (Web of Technology: Multidimensional Research Journal, 2024)
This article examines the impact of digital educational technologies on the modern educational process and the role of artificial intelligence technologies. The systems created on the basis of artificial intelligence are analyzed, including adaptive learning platforms, automated assessment systems and solutions for adapting the learning process to individuality. The article also discusses the issues of improving the effectiveness of learning through digital technologies, expanding access to education and reducing the burden on teachers. The article analyzes global trends in the field of digital technologies in the field of education and the possibilities of their application at the local level. The authors reflect on how to provide an individual approach using artificial intelligence technologies, as well as on ways to effectively use information in the educational process.